After-hours connectivity and its consequences: How work intrusions after hours induce employee silence and deceptive knowledge concealment - Xu, Caiyun; Chen, Chun-Shuo (Edelweiss Applied Science and Technology, 2026)
This study investigates the mechanism by which after-work work intrusion influences two critical organizational behaviors: employee silence and deceptive knowledge concealment. Based on Conservation of Resources Theory (COR) and Social Exchange Theory (SET), we construct and validate a theoretical model: non-work connectivity depletes employees' psychological resources, prompting protective silence and thereby increasing the likelihood of deceptive knowledge concealment. Using structural equation modeling (SEM) on survey data from 412 full-time employees in digitally intensive roles, results indicate that after-work connectivity significantly and positively predicts employee silence, which in turn significantly and positively predicts deceptive knowledge concealment, with after-work connectivity mediating this relationship. Furthermore, restorative experiences mitigate the impact of after-work connectivity on employee silence, while ethical climate weakens the promotional effect of employee silence on deceptive knowledge concealment. This study enriches theories in digital work and organizational behavior, offering practical recommendations for organizational managers in establishing post-work communication norms, promoting employee psychological recovery, and fostering ethical organizational climates.